Coping experiences of graduate students on full-time employment and full-time academic programmes (2020)
There are full-time employed graduate students who undertake full-time studies at universities in other countries but there is minimal documentation of such engagements in Ghana. This study explored the coping experiences of full-time workers who are pursuing full-time graduate studies in a Ghana higher institution. Purposeful sampling was deployed to recruit ten graduate students from whom information was gathered using one-on-one semi-structured interviews. Findings from the study revealed that the participants' inability to secure financial support for their studies and the need to consolidate their jobs were the key factors influencing their decision to combine full-time study and work. Results also showed that flexitime arrangements served as the best strategy for coping with the two full-time endeavours. Additional results indicated that focusing on one role at the expense of the other and some form of subtle support from superiors were motivators for the study subjects to cope with the dual roles. Moreover, it was apparent that these full-time working-students often experience compelling challenges as a result of their engagement which are potential reasons for employment dishonesty among such employees. The findings of this study are important for consideration among higher educational institutions, employers, policymakers, graduate students, and others.